2020
DOI: 10.38001/ijlsb.747883
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity of Musa acuminata Peel Extract against Gram-Positive Bacteria

Abstract: Particular communities are discarding banana (Musa acuminata) peels as household and industrial food waste. It is high in nutritive value and a healthy source of food to consume. This study aims to evaluate the antimicrobial activity of M. acuminata peels against four types of Gram-positive bacteria, namely, Bacillus cereus, Staphylococcus aureus, Streptococcus pneumoniae and Streptococcus pyogenes. The extract of M. acuminate peel was prepared using a soxhlet apparatus for ethanolic extract and rotary evapora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
5
0
1
Order By: Relevance
“…Sterile filter paper discs (6 mm) containing 10 µl of the fungal extracts were placed onto the agar plates. The plates were incubated at 37°C for 24 h and the zone of inhibition was measured to the nearest mm (Subramaniam et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Sterile filter paper discs (6 mm) containing 10 µl of the fungal extracts were placed onto the agar plates. The plates were incubated at 37°C for 24 h and the zone of inhibition was measured to the nearest mm (Subramaniam et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…who revealed that banana peel extract has the best antimicrobial activity and preservatives of banana peel extract are believed to be associated with phytochemical components of it, like phenolic and tannins as reported by [17]. However, the result was not the same with [13] reported that banana peel extract was not effective against all strains of Gram-positive bacteria. Also, [32] reported that banana peel extract is only effective against Agrobacterium tumefaciens, Other bacterial strains, on the other hand, demonstrated resistance to the extract-treated wood.…”
Section: Pomegranatementioning
confidence: 89%
“…However, it is not further involved in remarkable industrial applications, although it contains many beneficial compounds, such as carotenoids, alkaloids, steroids, saponin, flavonoids phenolics, glycosides, amines, vitamins, fibers, minerals and carbohydrates [12]. Banana peels were used as traditional medicine in diarrhea, dysentery, enteric infections, diabetes, promote wound healing, primarily from burns, and aid in the treatment or prevention of a wide range of illnesses [13].…”
Section: ‫ـــــــــــــــــــــــــــــــــــــــــــــــــــــــــــ...mentioning
confidence: 99%
“…These molecules, although effective from 15 to 20% [2]. The very wide uses of medicinal plants for centuries by humans for treating various common pathologies prompted researchers to study the activities and pharmacological properties of different plant metabolites to confirm its properties on the one hand and on the other hand to identify the active ingredients at the origin of these virtues and consequently the use of these natural medicines wisely in primary care systems [3][4][5]. Some plants can be a major source of drugs due to their richness in secondary metabolites, these make and remain the subject of many researches, in particular the research of new natural constituents such as phenolic compounds, saponosides, alkaloids and essential oils [6,7].…”
Section: Introductionmentioning
confidence: 99%